Sunday

August 30, 2015
Posted by **Jennifer** on Wednesday, December 3, 2008 at 11:10am.

2x^-2 - 5x^-1 - 3 = 0

2a^2 -5a - 3 = 0

(2a^2 - ) + ( a - ) = 0

I am stuck here please help.

- Intermediate Algebra -
**Reiny**, Wednesday, December 3, 2008 at 12:03pmis 2a^2 -5a - 3 = 0

supposed to be the simplified version of

2x^-2 - 5x^-1 - 3 = 0 ??

your first equation would be

2/x^2 - 5/x - 3 = 0

multiply each term by x^2

2 - 5x - 3x^2 = 0

3x^2 + 5x - 2 = 0

(3x-1)(x+2) = 0

x = 1/3 or x = -2

- Intermediate Algebra -
**Jennifer**, Wednesday, December 3, 2008 at 1:02pmyes that is the sinplified version of

- Intermediate Algebra -